2016
DOI: 10.1002/jbmr.2887
|View full text |Cite
|
Sign up to set email alerts
|

Links Between the Microbiome and Bone

Abstract: The human microbiome has been shown to influence a number of chronic conditions associated with impaired bone mass and bone quality including obesity, diabetes and inflammatory bowel disease. The connection between the microbiome and bone health, however, has not been well studied. The few studies available demonstrate that the microbiome can have a large effect on bone remodeling and bone mass. The gut microbiome is the largest reservoir of microbial organisms in the body and consists of over a thousand diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 98 publications
(184 reference statements)
2
147
0
Order By: Relevance
“…Studies of host-microbe interactions have identified many ways in which changes in the microbiome may influence distant organs, which I classify in three ways: regulation of nutritional absorption, regulation of the immune system at the gut endothelium, and translocation of microbes and molecular products of bacteria across the endothelial barrier and into the systemic circulation (Fig 1) [11]. …”
Section: Mechanisms Behind the Role Of The Microbiome In Bone And Joimentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of host-microbe interactions have identified many ways in which changes in the microbiome may influence distant organs, which I classify in three ways: regulation of nutritional absorption, regulation of the immune system at the gut endothelium, and translocation of microbes and molecular products of bacteria across the endothelial barrier and into the systemic circulation (Fig 1) [11]. …”
Section: Mechanisms Behind the Role Of The Microbiome In Bone And Joimentioning
confidence: 99%
“…Many clinical conditions that are associated with or contribute to the development of osteoporosis are also associated with changes in the gut microbiota [11]. However, to date there is only one report linking the microbiome to osteoporosis in humans: the gut flora in patients with osteoporosis (defined using bone mineral density (BMD)) was recently reported to be different from that of normal controls (microbiota assessed by analysis of fecal 16S rRNA) [28].…”
Section: Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Besides the fact that human microbes encounter environmental agents via inhaled, oral, or dermal routes before our own mammalian cells, the microbes also respond to external agents. This impacts the status of the microbiome, which in turn affects the host brain and neurological system (Dinan and Cryan 2016), gut (Imhann et al 2016), liver (Selwyn et al 2016), bone (Hernandez et al 2016), kidney (Pluznick 2016), endocrine organs and tissues (Kunc et al 2016), reproductive system (Nelson et al 2016), and immune system and host defense (Levy et al 2016;Brown and Clark 2017). Figure 1.…”
Section: The Human Superorganismmentioning
confidence: 99%
“…Wide health claims are made for both, but more work defining specific molecular mechanisms is needed. Using the example of bone health, modification (or restitution) of the gut microbiota via nutritional supplementation with prebiotics and probiotics appear to be a new promising therapeutic strategy for osteoporosis [9,17,18]. In theory, identification of taxa with specific cell biological or immunomodulatory activities could be candidates for potential probiotic supplementation to address multiple conditions.…”
Section: Microbiota-based Interventionsmentioning
confidence: 99%